(untitled) (Journal of Health, Population and Nutrition, 2014)
The purpose of this qualitative research was to explore the needs and difficulties of mothers who had multiple babies at Sakarya County by focusing on their breastfeeding experience. Ten mothers who gave birth to multiple infants participated in the study voluntarily. The framework method of data analysis was applied systematically both within and across cases, with categories and themes identified by reading transcripts of interviews. Major themes generated from focus narrative interviews are described. These themes are: willingness of mothers to breastfeed and continue, management of breastfeeding, use of pacifier, daily life, ?nstructions of healthcare personnel, and advices from practice of experienced mothers. This study showed that women were aware of the importance of mothers milk for their babies. They all, somehow, made intensive efforts to breastfeed their twins. Women who expect and/or have multiple babies need much more support and guidance, which may include advice for nutritional and daily care. DOI: http://dx.doi.org/10.3329/jhpn.v31i4.20049 J HEALTH POPUL NUTR 2013 Dec; 31(4): 504-509